2010
DOI: 10.1103/physrevlett.105.076401
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Mean Field Theory for Quench Dynamics in Correlated Electron Systems

Abstract: A simple and very flexible variational approach to the out-of-equilibrium quantum dynamics in strongly correlated electron systems is introduced through a time-dependent Gutzwiller wave function. As an application, we study the simple case of a sudden change of the interaction in the fermionic Hubbard model and find at the mean-field level an extremely rich behavior. In particular, a dynamical transition between small and large quantum quench regimes is found to occur at half-filling, in accordance with the an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

26
295
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 198 publications
(325 citation statements)
references
References 31 publications
26
295
0
4
Order By: Relevance
“…In several studies presented in the literature it was shown that a number of quantum isolated systems with short-range interactions reach a stationary state [17,18,20,21,30], while some fully-connected models [33,35,54] and some mean-field approximations to models with short-range interactions [55][56][57] keep a nonstationary behavior. For the isolated quantum Ising chain a stationary state is indeed reached after the quench and we will therefore focus on this relatively simple case.…”
Section: B Dynamic Correlations and Response Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In several studies presented in the literature it was shown that a number of quantum isolated systems with short-range interactions reach a stationary state [17,18,20,21,30], while some fully-connected models [33,35,54] and some mean-field approximations to models with short-range interactions [55][56][57] keep a nonstationary behavior. For the isolated quantum Ising chain a stationary state is indeed reached after the quench and we will therefore focus on this relatively simple case.…”
Section: B Dynamic Correlations and Response Functionsmentioning
confidence: 99%
“…However, their asymptotic stationary state should nonetheless be described by the so-called generalized Gibbs ensemble (GGE) in which each conserved quantity is characterized by a generally different effective temperature [17][18][19][20][21][22][23]. On the other hand, other works [24][25][26][27][28][29][30][31][32][33][34][35] have shown (or at least argued) that this scenario could actually be significantly richer.…”
mentioning
confidence: 99%
“…Again, in higher dimensions, appropriate approximations are necessary, such as a time-dependent Monte-Carlo method [52], time-dependent dynamical mean field theory [53][54][55][56][57], the Gutzwiller ansatz for fermions [58][59][60], the flow equation method [9,10,61,62], or effective quasi-particle methods [63].…”
Section: Introductionmentioning
confidence: 99%
“…We now turn to the 2D square lattice. The spreading of correlations in dimension higher than one constitutes an almost unexplored land where only mean-field methods have been applied so far [21][22][23][24][25][26]. The latter are reliable only in the unphysical limits of large lattice connectivity or large internal "flavor" degeneracy.…”
mentioning
confidence: 99%